A rare case of tuberculous choroidal abscess - Ravikumar K.; Arthi M; Rajakumari M (International Journal of Medical Research and Review, 2016)
We report a case of ocular tuberculosis which presented as a subretinal abscess along with an active choroiditis patch and disc edema but with subtle ocular symptoms. Patient had a strongly positive Tuberculin Skin Testing but negative Interferon Gamma Release Assay. Based on the diagnosis of presumed ocular tuberculosis the patient was started on Category 1 Anti tuberculous therapy with a tapering dose of oral steroids, to which the patient responded in 4 weeks with complete resolution of lesions. This is a rare manifestation of ocular tuberculosis with panoramic uniocular manifestations in an immunocompetent male which healed rapidly without any residual damage. This case is reported to emphasize the importance of early detection and management of ocular tuberculosis as it aids in lesser ocular morbidity and visual impairment.